The changing of assumptions and extended science (Polis (Santiago), 2018)
The author argues that modern scientific worldview is challenged to adapt to new evidence, which is of great difficulty for the dense network of theoretical assumptions on which it is involved. He clarifies that he does not aims to attack the spirit of science but motivate its own evolution, which should go in the direction of a more holistic science or science of totality, of which he describes its characteristics, for which believes that the time is ripe.
Keywords: scientific worldview; theoretical assumptions; holistic science; science of totality